Characterization of the microbiome of the invasive Asian toad in Madagascar across the expansion range and comparison with a native co-occurring species - Bárbara Santos; Molly C. Bletz; Joana Sabino-Pinto; Walter Cocca; Jean Francois Solofoniaina Fidy; Karen LM Freeman; Sven Kuenzel; Serge Ndriantsoa; Jean Noel; Tsanta Rakotonanahary; Miguel Vences; Angelica Crottini (PeerJ, 2021)
Biological invasions are on the rise, with each invader carrying a plethora of associated microbes. These microbes play important, yet poorly understood, ecological roles that can include assisting the hosts in colonization and adaptation processes or as possible pathogens. Understanding how these communities differ in an invasion scenario may help to understand the host’s resilience and adaptability. The Asian common toad, Duttaphrynus melanostictus is an invasive amphibian, which has recently established in Madagascar and is expected to pose numerous threats to the native ecosystems. We characterized the skin and gut bacterial communities of D. melanostictus in Toamasina (Eastern Madagascar), and compared them to those of a co-occurring native frog species, Ptychadena mascareniensis, at three sites where the toad arrived in different years. Microbial composition did not vary among sites, showing that D. melanostictus keeps a stable community across its expansion but significant differences were observed between these two amphibians. Moreover, D. melanostictus had richer and more diverse communities and also harboured a high percentage of total unique taxa (skin: 80%; gut: 52%). These differences may reflect the combination of multiple host-associated factors including microhabitat selection, skin features and dietary preferences.